Stardust - Gaiman, Neil. (London : Review, 1999)
Young Tristran Thorn, having lost his heart to the lovely but cold Victoria Forester, leaves the safe English town of Wall and sets out into a strange world on a quest to retrieve a fallen star he has promised to his beloved.
Keywords: Adventure fiction; Man-woman relationships -- England -- Fiction; Young man -- England -- Fiction